2018
DOI: 10.1007/s40618-018-0960-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of isolated maternal hypothyroxinemia during the first and second trimester of gestation on pregnancy outcomes: an intervention and prospective cohort study in China

Abstract: Objectives To explore the effect of isolated maternal hypothyroxinemia (IMH) during the first and second trimester of gestation on pregnancy outcomes. To explore whether levothyroxine (L-T4) treatment of women who had IMH identified in the first trimester improves pregnancy outcomes. Methods Women in the early pregnancy in the iodine-sufficient area ( n = 3398) were recruited to this prospective cohort study (ChiCTR-TRC-12002326). Serum thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 26 publications
1
51
2
Order By: Relevance
“…The articles were published in various geographical region: North America (15) and USA (14,20)], South America [Brazil (16)], Europe [Netherland (21,24,29), Spain (22), Finland (23) and Ireland (28)] and Asia / Australia [China (6,11,26,27) and Australia (25)]. All studies were prospective or retrospective cohorts and 47% (7/15) had a population-based design (21-23, 26, 27, 29, 30).…”
Section: Search Results Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The articles were published in various geographical region: North America (15) and USA (14,20)], South America [Brazil (16)], Europe [Netherland (21,24,29), Spain (22), Finland (23) and Ireland (28)] and Asia / Australia [China (6,11,26,27) and Australia (25)]. All studies were prospective or retrospective cohorts and 47% (7/15) had a population-based design (21-23, 26, 27, 29, 30).…”
Section: Search Results Study Selection and Characteristicsmentioning
confidence: 99%
“…Nine studies investigated the association of maternal IMH and gestational HTN, preeclampsia and eclampsia (6,11,14,16,20,(23)(24)(25)28). Neither preeclampsia nor eclampsia were associated with IMH diagnosed in rst or second trimesters of pregnancy; in addition, all the above studies except for two (6,11) found no signi cant association between maternal IMH and gestational HTN. Gong et al (2019) however reported that IMH identi ed in the second trimester was associated with increased risk of only gestational HTN, particularly among women with BMI < 25 kg/m 2 , (adjusted OR: 4.2, 95% CI: 1.61-10.96) (6).…”
Section: Feto-maternal Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the effects isolated hypothyroxinemia on gravidas and fetus. At present, there were few studies on the relationship between the isolated hypothyroxinemia and adverse pregnant outcomes, and the results of studies were controversies [29][30][31]. Some studies have reported increased risk of premature delivery, fetal distress, and premature rupture of membranes and higher mean birth weight in isolated hypothyroxinemia [32].…”
Section: Discussionmentioning
confidence: 99%